ANALISIS PELAKSANAAN REFORMASI BIROKRASI TINGKAT MIKRO PADA SEKRETARIAT JENDERAL MAJELIS PERMUSYAWARATAN RAKYAT REPUBLIK INDONESIA - Habsul Nurhadi (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2017)
This research inspired from the fact the low readiness of bureaucratic reform in the Secretariat General of the MPR-RI in 2013, as well as lack of the evaluation of bureaucratic reform in 2014, making it nearly did not get the performance benefits (remuneration). The study aims to find out how far the Secretariat General of the MPR-RI has been carrying out bureaucratic reform. This study adopted qualitative approaches, to dimension case study, presented in a descriptive, with between other uses the theory of reinventing government (1992) and the theory of banishing bureaucracy (1997). This research is naturalistic paradigm, where observation and data collection done just as there are. Based on data processing suggests that in generally the bureaucracy reform in the Secretariat General of the MPR-RI 2010-2014 still not fully way implementation guidelines for the bureaucratic reforms are already published by the Ministry of Administrative State Apparatus and Bureaucratic Reform.